PEMBELAJARAN EKSPRESI DIRI MELALUI HOBI BERBASIS PROYEK DALAM MODUL BAHASA INDONESIA KELAS V SEKOLAH DASAR - Hanny Khairiza Ahmad; Virja Gias Putri; Mayang Sari; Tara Dian Septio; Dwi Novita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Indonesian at the elementary school level does not only focus on developing language skills, but also on forming students' capacity to express themselves constructively. One of the right strategies to achieve this is a project-based learning approach that is integrated with students' interests and hobbies. This article aims to describe the application of learning self-expression through hobbies using the project method in the Indonesian language module for class V elementary schools. The method used is descriptive qualitative, by analyzing teaching modules designed based on student characteristics and PjBL principles. The results of the analysis show that project-based learning through hobbies can increase student participation in the learning process, self-confidence, and oral and written language skills. Thus, this module can be used as a meaningful and context-appropriate learning alternative in teaching Indonesian in elementary schools.